2018
DOI: 10.1016/j.psyneuen.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin releasing factor receptor 1 antagonists prevent chronic stress-induced behavioral changes and synapse loss in aged rats

Abstract: Mounting evidence suggests that chronic stress can alter brain structure and function and promote the development of neuropsychiatric disorders, such as depression and Alzheimer's disease. Although the results of several studies have indicated that aged brains are more vulnerable to chronic stress, it remains unknown whether antagonists of a key stress regulator, the corticotrophin releasing factor receptor 1 (CRF1), can prevent stress-induced anxiety and memory deficits in animal models. In this study, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Our results showing that the infusion of the CRHR1-selective antagonist R121919 into ovBNST can reverse maladaptive behaviors (Fig. 4) is therefore consistent with several reports testing systemic effects of CRH modulators (Heinrichs et al, 2002;Gutman et al, 2003;Micioni Di Bonaventura et al, 2014;Dong et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Our results showing that the infusion of the CRHR1-selective antagonist R121919 into ovBNST can reverse maladaptive behaviors (Fig. 4) is therefore consistent with several reports testing systemic effects of CRH modulators (Heinrichs et al, 2002;Gutman et al, 2003;Micioni Di Bonaventura et al, 2014;Dong et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…These authors also showed that chronic administration of antalarmin ( a CRH-R1 antagonist ) significantly decreased plasma corticosterone levels, tissue Aβ 1–42 levels and Aβ plaques deposition in the brain, and blocked the effects of isolation stress on anxiety levels and memory (Dong et al, 2014). A few years later, a 3 month-treatment in food with CRH-R1 antagonists ( Antalarmin and R121919 ) was shown to prevent stress-induced behavioral changes ( anxiety and memory ) and synaptic loss in aged rats, perhaps by reversing HPA axis dysfunction (Dong et al, 2018). Moreover, in another mouse model of AD ( APP/PS1 ) a 5 month-treatment with R121919 prevented the onset of cognitive impairment, reduced cellular and synaptic deficits and Aβ levels (Zhang et al, 2016).…”
Section: Hpa Axis: Multiple Promising Targets For Ad Treatmentmentioning
confidence: 99%
“…For example, potential clinical applications of CRF1 receptor antagonists include the treatment of anxiety, allergy, autoimmune inflammatory disorders, epilepsy and so on (Grammatopoulos and Chrousos, 2002). In aged rats, two CRF1 receptor antagonists, R121919 and antalarmin, prevented chronic stress-induced anxiety-related behavioral and memory deficits (Dong et al, 2018). Although CRF1 receptor antagonists show promising effects in rodents, their clinical efficacy is mixed.…”
Section: Crf1 Antagonists and Other Antidepressantsmentioning
confidence: 99%